38. RELATIONSHIP WITH TIME SPENT USING SMARTPHONES AND THE MYOPIA IN ETHNIC BOARDING HIGH SCHOOL STUDENTS IN VINH CITY, NGHE AN PROVINCE. YEAR 2023-2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the time spent using smartphones and the relationship with myopia in ethnic boarding high school students. Subjects and methods: Cross-sectional descriptive study on 1558 students at 2 ethnic boarding high schools in Vinh city, Nghe An province from September 2023 to the end of March 2024.Results: All students use smartphones more than 1 hour/day, of which 56.58% of students use smartphones more than 3 hours/day, the average usage time is 3.36 hours/day. Female students have an average usage time of 4.08 hours/day, 3.02 hours/day higher than male students (p
Keywords: myopia; smartphone use time; high school students